THE CONSCIOUS CORPORATE GROWTH PRACTICE (CCG). A QUALITATIVE RESEARCH AIMED TO VERIFY THE APPLICATION OF VIRTUE ETHICS IN BUSINESS - Carrassi, Mario (European Scientific Journal, ESJ, 2014)
Alienation at work is one of the most pervasive phenomenon of the post-industrial society and management in both the private and public sectors are engaged in a constant struggle against it. In this paper, we suggest that Reflective thinking can emphasize informal learning and personal vision through the investigation of the intentions that sustain both personal and company’s actions and both individual and collective behaviours. This practice is suggested to enhance the degree of awareness in the organization and to shed light on the level of influence and on the mutual relationship with the environment. (Carrassi, 2013) This is the product of the activation of a fruitful relationship between all the variables of the business environment, that lead to economic prosperity, satisfaction and simultaneous fulfilment of individuals, stakeholders, and the environment. The present study, through a qualitative research approach, aims to examining the hypothesis of the Conscious Corporate Growth practice. Two companies were interviewed. The research focused on investigating issues related to virtue ethics as a practical approach to business management. To meet these objectives, seven major areas of inquiry were examined A number of interesting patterns of results were revealed through the content analysis of the responses. Based on the results, the worth of the CCG practice has been confirmed in regards to its application to small family business. A series of propositions stimulate future research efforts.